1986
DOI: 10.1126/science.3961493
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroendocrine Thymus: Coexistence of Oxytocin and Neurophysin in the Human Thymus

Abstract: Immunoreactive oxytocin and neurophysin were identified and measured by radioimmunoassay in human thymus extracts. Serial dilutions of extracts paralleled the appropriate standard curves. Thymus-extracted oxytocin and neurophysin eluted in the same positions as reference preparations on Sephadex G-75. Authenticity of oxytocin was confirmed by biological assay and high-performance liquid chromatography analysis. In most instances, thymus contents of oxytocin and neurophysin were far greater than those expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
7

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(88 citation statements)
references
References 21 publications
2
79
0
7
Order By: Relevance
“…Unlike the short half-life of exogenous supplements of oxytocin, the plasma elevations seen in the present mice are a consistent and reproducible effect [30], making bacteria or bacterial products a possible therapy for mental health. It remains to be proven whether microbe-induced oxytocin in these murine models originates primarily from the hypothalamus or from other peripheral sources [72][73][74][75][76]. Nonetheless, our results suggest that gut bacteriainduced oxytocin may explain data linking gut microbiome dysbiosis with neuropsychological disorders, including autism [77,78].…”
Section: Discussionmentioning
confidence: 92%
“…Unlike the short half-life of exogenous supplements of oxytocin, the plasma elevations seen in the present mice are a consistent and reproducible effect [30], making bacteria or bacterial products a possible therapy for mental health. It remains to be proven whether microbe-induced oxytocin in these murine models originates primarily from the hypothalamus or from other peripheral sources [72][73][74][75][76]. Nonetheless, our results suggest that gut bacteriainduced oxytocin may explain data linking gut microbiome dysbiosis with neuropsychological disorders, including autism [77,78].…”
Section: Discussionmentioning
confidence: 92%
“…The thymic repertoire of neuroendocrine-related polypeptide precursors has been proposed to recapitulate at the molecular level the dual physiologic role played by the thymus in T-cell development [8][9][10]. With a special regard to the neurohypophysial peptide family, our group as well as others have shown that thymic epithelial and nurse cells (TEC/TNC) synthesize oxytocin (OT) and its precursor-associated protein, OT-neurophysin [11,12]. Thymic OT plays a dual role in T-cell selection.…”
Section: Introductionmentioning
confidence: 99%
“…This latter can explain why is enhanced thymulin secretion of epithelial cells by it. Pituitary hormones -prolactin, luteinizing and follicle stimulating hormones, corticotropin releasing factor, oxytocin, and vasopressin -are also synthesized by the thymus cells [1,[52][53][54][55], and the cells have pituitary hormone receptors [56].…”
Section: Effect Of Thymic Self-hormones On Non-immune Cells and Functmentioning
confidence: 99%